Valuation of interest-sensitive financial instruments : - Babbel, David F. (Society of Actuaries Schaumbug, 1996)
Valuations of Interest-Sensitive Financial Instruments provides in-depth analysis of the development and underpinnings of models that are essential to the financial analyst or valuation actuary. Complete coverage includes: spot and forward interest rates, discrete- and continuous-time one-factor models, multi-factor discrete- and continuous-time models, and simulation approaches.